Occupational asthma in a fruit and vegetables vendor - Baldassarre, Antonio; Dragonieri, Silvano; Luisi, Vito; Musti, Marina; Vimercati, Luigi (La Medicina del Lavoro, 2016)
Background: This study presents a case report of a woman running a fruit and vegetables market stall, occupationally exposed to mushroom spores, who developed asthmatic symptoms. Basidiospores are allergens that can give rise to sensitization and subsequently trigger an allergic reaction, such as contact dermatitis, rhino-conjunctivitis, asthma and hypersensitivity pneumonitis. Methods: A 40-year-old atopic woman, who had worked at a market stall selling fruit and vegetables for the past 26 years in a small town market in southern Italy, came to our attention at the Occupational Medicine Unit, complaining of a 3-year history of dyspnoea, cough, and wheezing during autumn and winter. Results: Spirometry showed a severe mixed type respiratory deficit with a significant bronchodilator response obtained with salbutamol administration. Skin prick tests to common aeroallergens were negative. Prick-to-prick test with fresh Pleurotus ostreatus was positive. We evaluated the size of the skin wheals and compared them to the positive control according to the Skin Index. An on-the-spot inspection of her store was performed and environmental conditions were identified that did not allow a satisfactory air exchange. Conclusions: The clinical history and the results of the allergologic investigations, plus an on-the-spot inspection, permitted us to ascertain that this subject had developed occupational asthma due to Pleurotus ostreatus spores. We advised her to stop handling and selling mushrooms, and she has no longer suffered asthmatic symptoms, over seven years of follow-up, and regularly continued to work without needing to take anti-asthma drugs.